The Effect of Learning Model STAD (Student Team Achievement Division) Assisted by Media Quizizz on Motivation and Learning Outcomes in Class XI Indonesian History Subjects at SMA Trimurti Surabaya - Yulianto, Iwan; Warsono, Warsono; Nasution, Nasution; Rendy A.P, Dwi Bagus (Universitas Malikussaleh, 2020)
Social studies education as a science combines a number of selected concepts from branches of social science and other sciences. Students are less motivated in learning history. This condition arises because the variation in historical learning is still lacking because teachers only use traditional methods that place the teacher as the center of information. The Quizizz media-assisted STAD model has the potential to overcome the problems of motivation and student learning outcomes at Trimurti High School. The study was conducted to determine the effect of the STAD (Student Team Achivement Division) learning model assisted by the Quizizz media on motivation and learning outcomes in Indonesian History subjects class XI at Trimurti High School Surabaya. This research is an experimental study using pretest-posttest control group design. The treatment in the experimental class was the application of the STAD (Student Team Achievement Division) learning model assisted by the Quizizz media and the direct learning model (MPL) applied to the control class also assisted by the Quizizz media. T test shows the value of sig 0.03 <0.05, so there are differences in the value of the motivation of students in the control class with the experimental class. T test shows the value of sig 0.002 < 0.05, so there are differences in the value of student learning outcomes in the control class with the experimental class.